Factors Influencing Musculoskeletal Disorders (MSDs) in Oil Palm Field Workers - Rahman, Fadlul Syahidur; Rahmanto, Safun; Yuliadarwati, Nungki Marlian (Universitas Ibn Khaldun Bogor, 2024)
Musculoskeletal Disorders (MSDs) are perceived pain in the musculoskeletal system. Musculoskeletal symptoms occur due to injury or disruption of the musculoskeletal system caused by repeated exposure and interference with the normal function of tissues. The musculoskeletal system includes all muscule, bones, tendons, ligaments, blood vessels, joints, intervertebral discs, and others. Discomfort arising in soft tissues, especially muscles, is more common than in bones and joints. The aim of this research is to analyze the significant influence of age, duration of work, and smoking habits or behavior on the occurrence of Musculoskeletal Disorders (MSDs) among field workers in oil palm plantation at PT. Yudha Wahana Abadi, the type of this research is quantitative with a cross-sectional approach, a sample of 150 field workers, which was determined by simple random sampling techniques, the statistical test used was logistic regression, the research instrument is a questionnaire. The findings indicated that the age, duration of work, and smoking habits were found to not have a statistically significant effect on the likelihood of experiencing Musculoskeletal Disorders (MSDs) among the field workers in the oil palm plantation at PT. Yudha Wahana Abadi with the results of logistic regression analysis obtained (age p-value = 0,230>0,05), (duration of work p-value = 0,419>0,05), (smoking habits p-value = 0,797>0,05). Based on the results of the analysis of 150 field workers in oil palm plantation, it is known that who need an improvement totaled 24 and who doesn’t need an improvement totaled 126 . this research concludes that age, duration of work, and smoking habits were found to not have a statistically significant effect on field workers oil palm plantation in PT. Yudha Wahana Abadi. Advice for palm oil plantation’s field workers is to pay more attention to ergonomical posture and safety at the field so that they can prevent Musculoskeletal Disorders (MSDs) from occurring quickly.